(untitled) (Al-Academy, 2024)
Ancient and contemporary ceramic formation addresses the issue of the relationship between it and the concept of violence by expressing its manifestations, first in formal composition, and recording the real features, as a result of the conflict that man experiences. Its importance has emerged, among the ceramic arts, in particular, in terms of formal compositions and color techniques, as well as its methods, which made it have dimensions, sometimes unrealistic, characterized by strong expression, and a dynamic rhythm, clear through its circulation and movement within society. In addition to its creative design lines resulting from the process of stimulating the imagination, in which it achieved inspiration and symbolism, and presented more vibrant models, in which the female ceramic formation became one of the elements, repeated in expressing the concept of (violence), it has a special power of influence, as it provides advertising propaganda. Through diacritical marks, towards a positive life, under a new perspective of social relations. Shedding light on these ceramic formations is an acknowledgment of their importance, and for the purpose of presenting a new reading of their implications in contemporary art.